Lightweight By-Product Block for Road Construction Application - Paizol Akman, Muhammad Afzal; TUAN ISMAIL, TUAN NOOR HASANAH (Progress in Engineering Application and Technology, 2024)
The road construction industry in Malaysia and numerous other nations has encountered formidable challenges, chiefly emanating from soft soils. Lightweight block technology has garnered significant interest in addressing such challenges owing to its reduced weight, which minimizes pressure on the underlying soil, ameliorates differential settlement, facilitates ease of handling and installation, and aligns with sustainable construction practices. Therefore, this research was carried out to explore the feasibility of local by-product wastes in developing an alternative lightweight block for road construction applications. In this research, palm kernel shells (PKS) and rice husk (RH) were used as alternative lightweight aggregates (LWA) in the development of lightweight by-product blocks to reduce their density. The mix design ratio for the lightweight by-product block is 2:1:1 (cement:sand:aggregate). In this research, RH is partially replaced with sand by (0%,25%,50%,75%, and 100%) while PKS is replaced with coarse aggregate. The mixture was poured into a cube mould 50X50X50mm and underwent 7, 14, and 28 days of air-dry curing. The performance of the lightweight by-product block was evaluated based on density, water absorption, compressive strength, and Young’s modulus. The results have shown that the higher the proportion of RH is, the lower its compressive strength the lighter its density, and the high in water absorption. RH proportions of 25% and 50% show a good result before dropping dramatically; the compressive strength is 4 MPa and 2.64 MPa, respectively. The density achieved is 1642.37 kg/m3 and 1460.03 kg/m3 respectively.